Studi UX pada Aplikasi Edukasi Berbasis Android Menggunakan Heuristic Evaluation - Alvianus Artha Desienda; Didik Setya Nugraha; Farhan Afrian Nanda (Jurnal Sistem Informasi Komputer ( SIKOM ), 2024)
The rapid growth of Android-based educational applications requires careful attention to user experience (UX) to ensure effective and comfortable digital learning processes. Ruangguru is one of the most widely used educational applications in Indonesia and continues to undergo interface and feature updates. Therefore, an evaluation of the latest version of the application is necessary to assess its usability quality. This study aims to evaluate the user experience of the Ruangguru application using Nielsen’s Heuristic Evaluation method. The research employs a qualitative descriptive approach through independent observation without involving respondents. The evaluation was conducted by directly observing the latest version of the Ruangguru application on an Android device and assigning scores to each of the ten usability heuristics. The results indicate that most heuristic principles have been well implemented. Principles such as Visibility of System Status, Consistency and Standards, User Control and Freedom, and Aesthetic and Minimalist Design received high scores, as the application provides clear system feedback, consistent navigation, sufficient user control, and a clean interface design. Overall, the Ruangguru application achieved an average score of approximately 4.0 out of 5, indicating good usability quality. However, improvements are still required in the Error Prevention principle, as the system does not fully prevent user errors before they occur. The findings of this study are expected to provide useful insights and recommendations for developers to further enhance the user experience of the Ruangguru application in future development.